Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1080/13632430903152302
|View full text |Cite
|
Sign up to set email alerts
|

The appraisal of teachers' performance and its impact on the mutuality of principal-teacher emotions

Abstract: The current study examines the mutual discrete emotions among superiors and their above-and below-average workers within a hierarchical organisation (school). Using a survey method within a random sample of 40 elementary schools in Northern Israel, each principal and four of his or her teachers (two who had been appraised as excellent and two who had been appraised as poorperforming) completed two questionnaires which addressed the teachers' perceived performance and emotions toward the principal/teacher. As e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
1
10
0
5
Order By: Relevance
“…When the literature is reviewed, performance and performance evaluation are handled with many concepts such as: organizational commitment (Swailes, 2002); organizational citizenship (Podsakoff, MacKenzie, Paine & Bachrach, 2000); organizational culture (Biswas, 2009;Harwiki, 2013;Jung & Takeuchi, 2010;Ogbonna & Harris, 2000); organizational climate (Litwin and Stringer, 1968); stress (Kakkos & Trivellas, 2011;Kazmi, Amjad, & Khan, 2008;Khalid, Murtaza, Zafar, Zafar, Saqib, & Mushtaq, 2012); burnout (Garden, 1991;Taris, 2006); motivation (Kunz & Pfaff, 2002); organizational learning (Garcia-Morales, Jimenez-Barrionuevo and Gutierrez-Gutierrez, 2012, Montes, Moreno, & Garcia-Morales, 2005); conflict management (Kotlyar, 2001;Wakefield, Leidner, & Garrison, 2008); organizational justice (Williams, 1999;Zehir, Akyüz, Eren, & Turhan, 2013); school culture (Heck & Marcoulides, 1996;Maslowski, 2001), organizational trust (İşleyen, 2011), teacher education (Ferguson & Womack, 1993;Pecheone & Chung, 2006), leadership style (Danişman, Tosuntaş & Karadağ, 2015); quality of life (Bektaş, 2013). At the same time, there are studies on performance evaluation such as teachers and administrators' opinions (Altun & Memişoğlu, 2008;Alpaslan, 2015;Soydan, 2012;Süzen, 2007;Tamam, 2005;Yariv, 2009); performance evaluation tools (Flowers & Hancock, 2003;Gün, 2012;Koçak, 2006); and performance evaluation methods…”
Section: Professional Responsibilitymentioning
confidence: 99%
“…When the literature is reviewed, performance and performance evaluation are handled with many concepts such as: organizational commitment (Swailes, 2002); organizational citizenship (Podsakoff, MacKenzie, Paine & Bachrach, 2000); organizational culture (Biswas, 2009;Harwiki, 2013;Jung & Takeuchi, 2010;Ogbonna & Harris, 2000); organizational climate (Litwin and Stringer, 1968); stress (Kakkos & Trivellas, 2011;Kazmi, Amjad, & Khan, 2008;Khalid, Murtaza, Zafar, Zafar, Saqib, & Mushtaq, 2012); burnout (Garden, 1991;Taris, 2006); motivation (Kunz & Pfaff, 2002); organizational learning (Garcia-Morales, Jimenez-Barrionuevo and Gutierrez-Gutierrez, 2012, Montes, Moreno, & Garcia-Morales, 2005); conflict management (Kotlyar, 2001;Wakefield, Leidner, & Garrison, 2008); organizational justice (Williams, 1999;Zehir, Akyüz, Eren, & Turhan, 2013); school culture (Heck & Marcoulides, 1996;Maslowski, 2001), organizational trust (İşleyen, 2011), teacher education (Ferguson & Womack, 1993;Pecheone & Chung, 2006), leadership style (Danişman, Tosuntaş & Karadağ, 2015); quality of life (Bektaş, 2013). At the same time, there are studies on performance evaluation such as teachers and administrators' opinions (Altun & Memişoğlu, 2008;Alpaslan, 2015;Soydan, 2012;Süzen, 2007;Tamam, 2005;Yariv, 2009); performance evaluation tools (Flowers & Hancock, 2003;Gün, 2012;Koçak, 2006); and performance evaluation methods…”
Section: Professional Responsibilitymentioning
confidence: 99%
“…İlgili alanyazın incelendiğinde öğretmen performansı ve veli etkinlikleri (Aydemir, 2008), iş doyumu (Koç, Yazıcıoğlu ve Hatipoğlu, 2009 ve Yazıcıoğlu, 2010), insan kaynakları (Akyol, 2008) ve öğrenci görüşleri (Tüfekci, 2008) arasındaki ilişkileri inceleyen bir dizi araştırmanın yapıldığı görülmektedir. Ayrıca öğretmen performans yönetimi (Bostancı, Yolcu ve Şap, 2010;Boyacı, 2003;Çolak, 2007;Şentuna, 2007) ve öğretmen performansı değerlendirme (Alghanabousi, 2010;Cihantimur, 2006;Cooper, 2005;Duran, 2008;Harris ve Sass, 2012;Lamm, 1990;Miller, 2009;Tonbul, 2008;Yariv, 2009) konularını inceleyen çalışmalar yapılmıştır. Öğretmen performansını teşvik (Eberts, Hollenbeck ve Stone, 2002;Miller, 2011;Mitchell, 2009), öğrenci başarısı (Eisenberg, 2008;Spiggle, 2003;Washington, 2011), öğretmen geçmişi, kişilik özellikleri, sosyo-ekonomik statü (Bowers, 2006) ve ücret (Muralidharan ve Sundararaman, 2009) açısından ele alan çalışmalar olduğu görülmüştür.…”
Section: İşgören Performansıunclassified
“…Using questionnaires, Yariv (2009) investigated five individuals in each of 40 public elementary schools in Israel: the principal and two above-average-and two below-average-performing teachers. Findings showed that principals expressed highly positive emotions toward the high-performing teachers, including pride, appreciation, gratitude, happiness, and hope.…”
Section: Mission-related Factorsmentioning
confidence: 99%